Use of a rapid electronic survey methodology to estimate blood donors' potential exposure to emerging infectious diseases: Application of a statistically representative sampling methodology to assess risk in US blood centers. Issue 9 (3rd August 2020) - Whitaker, Barbee I.; Walderhaug, Mark; Hinkins, Susan; Steele, Whitney R.; Custer, Brian; Kessler, Debra; Leparc, German; Gottschall, Jerome L.; Bialkowski, Walter; Stramer, Susan L.; Dodd, Roger Y.; Crowder, Lauren; et al.
Background: Risk assessments of transfusion‐transmitted emerging infectious diseases (EIDs) are complicated by the fact that blood donorsʼ demographics and behaviors can be different from the general population. Therefore, when assessing potential blood donor exposure to EIDs, the use of general population characteristics, such as U.S. travel statistics, may invoke uncertainties that result in inaccurate estimates of blood donor exposure. This may, in turn, lead to the creation of donor deferral policies that do not match actual risk. Study Design and Methods: This article reports on the development of a system to rapidly assess EID risks for a nationally representative portion of the U.S. blood donor population. To assess the effectiveness of this system, a test survey was developed and deployed to a statistically representative sample frame of blood donors from five blood collecting organizations. Donors were directed to an online survey to ascertain their recent travel and potential exposure to Middle East respiratory syndrome coronavirus (MERS‐CoV). Results: A total of 7128 responses were received from 54 256 invitations. The age‐adjusted estimated total number of blood donors potentially exposed to MERS‐CoV was approximately 15 640 blood donors compared to a lower U.S. general population‐based estimate of 9610 blood donors. Conclusion: The structured donor demographic sample–based data provided an assessment of blood donorsʼ potential exposure to an emerging pathogen that was 63% larger than the U.S. population–based estimate. This illustrates the need for tailored blood donor–based EID risk assessments that provide more specific demographic risk intelligence and can inform appropriate regulatory decision making.